Some Fiscal Implications of Monetary Policy - Kevin Salyer; Harris Dellas (University of California, Department of Economics, 2001)
We study the implications of alternative monetary targeting procedures for real interest rates and economic activity. We find that countercyclical monetary policy rules lead to higher real interest rates, higher average tax rates, lower output but lower variability of tax rates and consumption relative to procyclical rules. For a country with a high level of public debt (e.g. Italy), the adoption of a counter cyclical proceedure such as interest rate pegging may conceivably raise public debt servicing costs by more than half a percentage point of GNP. Our analysis suggests that the current debate on the targeting proceedures of the European Central Bank ought to be broadened to include a discussion of the fiscal implications of monetary policy.
Keywords: 330; Geldpolitik; Realzins; Einkommensteuer; Konjunkturpolitik; Theorie